2019
DOI: 10.3897/bdj.7.e38492
|View full text |Cite
|
Sign up to set email alerts
|

Continental data on cave-dwelling spider communities across Europe (Arachnida: Araneae)

Abstract: Spiders (Arachnida: Araneae) are widespread in subterranean ecosystems worldwide and represent an important component of subterranean trophic webs. Yet, global-scale diversity patterns of subterranean spiders are still mostly unknown. In the frame of the CAWEB project, a European joint network of cave arachnologists, we collected data on cave-dwelling spider communities across Europe in order to explore their continental diversity patterns. Two main datasets were compiled: one listing all subterranean spider s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…The nomenclature follows Stoev et al (2008), Witt andRonkay (2011), Schönhofer (2013), The World Spider Catalog (2019), Frost (2019), and Hutson et al (2019). The taxa newly found in the cave are marked with an asterisk (*).Comments on the distribution of cave-dwelling spiders are in accordance with Deltshev (2008), Naumova et al (2016a), and Mammola et al (2019a, b), who have reported a total of 416 species for Balkan caves.…”
Section: Methodssupporting
confidence: 78%
“…The nomenclature follows Stoev et al (2008), Witt andRonkay (2011), Schönhofer (2013), The World Spider Catalog (2019), Frost (2019), and Hutson et al (2019). The taxa newly found in the cave are marked with an asterisk (*).Comments on the distribution of cave-dwelling spiders are in accordance with Deltshev (2008), Naumova et al (2016a), and Mammola et al (2019a, b), who have reported a total of 416 species for Balkan caves.…”
Section: Methodssupporting
confidence: 78%
“…R. Soc. B 286: 20191579 dataset of subterranean spider communities across Europe are available in an associated data paper [32] and updated as long as new data becomes available.…”
Section: Discussionmentioning
confidence: 99%
“…We compiled what we believe to be the first continental-scale georeferenced dataset of subterranean spider communities across Europe [32]. The dataset comprises data from 475 caves from 27 European countries, and covers a latitudinal range from 35°to 70°(figure 1).…”
Section: Methods (A) Dataset Assemblagementioning
confidence: 99%
“…For example, prolonged monitoring may help to understand the impact of specific environmental changes 17 19 , allowing to forecast future scenarios and promptly act to protect endangered species 20 22 . In this regard, the production of comparable datasets through time is of key importance 9 , 23 , 24 . However, data collection may not always be an easy task.…”
Section: Background and Summarymentioning
confidence: 99%